BUSINESS EDUCATION STUDENTS’ PERCEIVED INFLUENCEOFCURRICULUM INFORMATION HANDBOOK ON CHOICEOFCAREER PATHWAYS IN TERTIARY INSTITUTIONS (NAU Journal of Technology and Vocational Education, 2024)
This study explored perceived influence of curriculum information handbook of business educationon students’ choice of career pathways as regards their course selections in tertiary institutions inAnambra State. One research question guided the study, and one null hypothesis was tested at 0.05level of significance. Descriptive survey research design was adopted. The study was carried out infour public tertiary institutions in Anambra State. The population of the study comprised 902 businesseducation students and a sample size of 277 was drawn from the population. An 8-itemquestionnairewas used for data collection, which was validated by experts in the field of education. The Cronbach’salpha method was used to test the reliability, resulting in 0.79 reliability coefficient. Data analysis wasdone using mean, standard deviation and t-test. The findings revealed that curriculuminformationhandbook of business education provides enough information that helps students to understandthevarious career pathways inherent in business education and in their career pathway decision-makingwith respect to their course selections. Consequently, it was concluded that business educationdepartment should provide updated handbooks to enable the students make informed and quickerdecision relating to their career
Keywords: Business education graduates